Challenges and Coping Strategies of Teachers in Developing Self-Learning Modules - Rasaga, Daryl Rey (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the challenges and coping strategies of teachers in developing self-learning modules during the COVID-19 pandemic. Specifically, it examined how teachers developed self-learning modules, the challenges they encountered, the coping mechanisms they used, and the implications drawn from their experiences. The study was anchored on interpretivism, constructivism, and the Materials Design Model, which emphasizes the development of instructional materials based on learners’ needs, interests, and learning tasks. A qualitative case study design was employed at Liloan Central School, Liloan, Bonifacio, Misamis Occidental, during the school year 2020–2021. The participants were nine teachers directly involved in developing self-learning modules, selected through total enumeration. Data were gathered using an interview guide and analyzed through transcription, classification, and thematic interpretation. Findings revealed that teachers developed self-learning modules by following DepEd’s prescribed format, considering learners’ learning styles and capacities, and relying on self-commitment. The main challenges encountered were insufficiency of resources, limited internet access, and poor writing skills. To cope with these challenges, teachers searched for additional resources and sought assistance from school heads, colleagues, division personnel, ICT personnel, and other experts. The study concludes that self-learning modules became essential in sustaining quality education during the pandemic despite difficulties in preparation. The study supports SDG 4, Quality Education, and SDG 3, Good Health and Well-Being, as it promotes learning continuity while reducing health risks from face-to-face instruction. Its sustainability impact lies in strengthening educational, institutional, technological, and community resilience during crisis-based learning disruptions.